Josephine’s Effort to be a Woman Writer in Louisa May alcott’s Little Women:Liberal Feminist Perspective (LITERA KULTURA : Journal of Literary and Cultural Studies, 2018)
Abstract This study aims at revealing the traditional women values reflected in Victorian era and how Josephine resist the traditional values of women to be a woman writer in Louisa May Alcott’s Little Women.This literary study employs the concept of liberal feminist theory which dedicate to Josephine character and being an opposite figure as an ideal woman in her society. The main data of this study were taken from Little Women novel in the form of quotation that represents the problems of the study. Based on the analysis, this study reveals that in order to pursue her dream Josephine demonstrated her resistance towards the traditional women’s values such as piety, purity, submissiveness and domesticity. Her resistance also showed her different characteristics as a real lady as a stereotype in her society. Her being different in personality also influenced herself to be a woman writer. Keywords: Feminism, Liberal Feminism, Patriarchal, Victorian Era, and Woman Writer. Abstrak Tujuan ditulisnya studi ini adalah untuk mengungkapkan nilai-nilai tradisional perempuan yang tercermin dalam era Victoria dan bagaimana Josephine menolak nilai-nilai tradisional perempuan agar dapat diterima sebagai seorang penulis wanita di Little Women yang ditulis oleh Louisa May Alcott. Studi ini menggunakan konsep teori feminisme liberal yang mendedikasikan karakter Josephine dan menjadi sosok yang berlawanan sebagai wanita ideal dalam masyarakat itu. Data utama penelitian ini diambil dari novel Little Women dalam bentuk kutipan yang mewakili permasalahan penelitian. Berdasarkan hasil analisis, penelitian ini menunjukkan bahwa: Untuk mengejar mimpinya, Josephine menunjukkan perlawanannya terhadap nilai-nilai tradisional wanita seperti kesalehan, kemurnian, ketaatan dan kerumahtanggaan. Perlawanannya juga menunjukkan karakteristiknya yang berbeda sebagai wanita ideal yang dimerupakaan stereotype di masyarakatnya. Perbedaan kepribadiannya juga mempengaruhi dirinya untuk menjadi seorang penulis wanita. Kata kunci: Feminisme, Feminisme Liberal, Patriarkal, Era Victoria, Penulis Wanita.